A study in patients of median arcuate ligament syndrome undergoing laparoscopic management - Patel, Sahil M.; Nathani, Prakher B.; Dholariya, Meet V.; Kuswaha, Manoranjan R. (International Surgery Journal, 2024)
Median arcuate ligament syndrome (MALS), a rare disease characterized as a result of extrinsic compression by diaphragmatic fibers arching on the celiac artery. This syndrome presents a challenging diagnostic workup due to its various clinical presentations and incomprehensible pathophysiology, requiring various investigations to exclude other causes. Laparoscopic surgery is gaining popularity. The aim was to study presenting age, sex, clinical symptoms, postoperative symptom relief and re-establishment of celiac artery blood flow after laparoscopic surgery. The prospective study was carried out in a tertiary care hospital for 10 cases of MALS over 24 months. All patients underwent extensive evaluation with no definitive diagnosis and persistent symptoms. Radiologically proven cases were operated laparoscopically and post-operative celiac artery Doppler was done on 6 months follow-up. All demographic data, clinical characteristics, diagnostic studies, management and outcomes were reviewed. 70% cases of MALS present between 3rd to 5th decades with 85% female preponderance. Postprandial epigastric pain, most common presenting symptom in 60% cases. Laparoscopic surgery is extremely effective and considered to be safe, having substantial reduction in symptoms in 90% patients and re-establishment of celiac artery blood flow (PSV) in 100% patients on 6 months follow-up. Surgeons evaluating patients with chronic abdominal pain should consider MALS as a differential diagnosis. Prompt diagnosis and treatment are critical for resolving symptoms and improving patients’ quality of life. Radiological investigations are pivotal in diagnosis and post-operative evaluation. Laparoscopic management is recommended due to its shorter postoperative stay, less post-operative pain and cosmetic suture line.